The Efficacy of Dequalinium Chloride Against Vulvovaginitis in Pregnancy - Mila Permata Sari; Djanas, Dovy; Putra, Andani Eka (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction: Vulvovaginitis affects pregnancy outcomes and managing it involves the use of metronidazole or nystatin, which can cause local or systemic side effects. Dequalinium chloride (DQC) is suggested as a new treatment option for vulvovaginitis during pregnancy with minimal side effects. Objective: To compare the effectiveness of dequalinium chloride (DQC) versus metronidazole + nystatin (MN) in treating vulvovaginitis in pregnant women during their second and third trimesters. Method: A single-blind randomized controlled trial was conducted at the Andalas Public Health Center, Padang, from January to May 2024. Pregnant women in their second and third trimesters, meeting the inclusion and exclusion criteria, were enrolled. The participants were randomly assigned to either the DQC or MN group. Vaginal swabs were taken before and after a 6-day treatment, and PCR analysis was performed. Results: Eighteen patients were treated with DQC and MN. Most participants had bacterial vaginosis (DQC 78%, MN 83%), with half having candidiasis (DQC and MN 50%) and fewer cases of trichomoniasis (28% in both groups). Significant improvements were seen in the DQC group for symptoms (p=0.000), Gardnerella vaginalis (p=0.035), and Candida albicans (p=0.021). In the MN group, significant improvements were noted for symptoms (p=0.000) and Gardnerella vaginalis (p=0.002). No significant differences were observed between the groups for symptom resolution or microbial reduction. Conclusion: DQC is as effective as metronidazole + nystatin in treating bacterial vaginosis and candidiasis in pregnancy. Keywords: Vulvovaginitis, pregnancy, dequalinium chloride, metronidazole, nystatin